Melancholy as a Plot-Forming Concept in Orhan Pamuk’s Novels - Egana Yashar kzy Dzhabbarova (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2022)
This article analyses the concept of “melancholy” and “post-imperial melancholy” in Orhan Pamuk’s novels. An attempt is made to consider the novelist’s work from the point of view of postcolonial and decolonial theories. The material of analysis is limited to his novels A Strangeness in My Mind (2016) and Istanbul: Memories and the City (2012). The crucial state of Pamuk’s characters and, consequently, the object of analysis is melancholy, which, on the one hand, can be interpreted as nostalgia for the former greatness of the Ottoman Empire and, on the other hand, is an example of an “aestheticised nostalgia” as a technique of decolonial aestheticism. The article also focuses on Pamuk’s own position as a cultural trickster, balancing between East and West in an attempt to find a balance. The author examines images of the “bouza” and the “dog” as symbols of the Ottoman Empire and analyses the dichotomy of the “Eastern man” vs the “European man”. On the one hand, Pamuk’s characters, like Pamuk himself, associate themselves with the European man, broadcasting the “Orientalist” view of the West as a backward space, on the other hand, they are representatives of Oriental culture and mentality, guardians of Turkish traditions and the history of their own city. The analysis makes it clear that the melancholy of the protagonists is primarily related to their personal past and childhood memories. It is the author’s attempt to return to his own past in order to find cultural and personal integrity, to discover the origins of self-identity, and to overcome his inner “coloniser”. Thus, Pamuk’s melancholy is inextricably linked with pride and beauty.